1. Not finding help here? Sign up for a free 30min tutor trial with Chegg Tutors
    Dismiss Notice
Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Abstract Algebra: isomorphism proof

  1. Apr 17, 2012 #1
    1. The problem statement, all variables and given/known data

    Let G be an abelian group of order n. Define phi: G --> G by phi(a) = a^m, where a is in G. Prove that if gcd(m,n) = 1 then phi is an isomorphism

    2. Relevant equations

    phi(a) = a^m, where a is in G
    gcd(m,n) = 1

    3. The attempt at a solution

    I know since G is an ableian group it is a commutative group (so ab=ba). Also since we have the special converse we know there exists a r, s \in G such that mr + ns = 1. They only way i know if proving an isomorphism is proving that it is one-to-one and onto and I'm not sure what to do with these puzzle pieces. Is there another way to prove isomorphisms?
     
  2. jcsd
  3. Apr 17, 2012 #2

    Dick

    User Avatar
    Science Advisor
    Homework Helper

    To start, try to show that if phi(a)=e (where e is the group identity) and a is not equal to e, then m and n have common divisor that is not 1. Consider the set {e,a,a^2,...,a^(m-1)}. Is it a subgroup of G?
     
    Last edited: Apr 17, 2012
  4. Apr 19, 2012 #3
    I think I proved the contrapositive,

    Let a be a non-zero nilpotent element in R such that a^m = 0. If psi(a) is 0, then a is in the kernel and we're done. Otherwise, psi(a) is non-zero, and psi(a)^m = psi(a^m) = psi(0) = 0, which means that psi(a) is a non-zero nilpotent element of the image.
     
  5. Apr 19, 2012 #4

    Dick

    User Avatar
    Science Advisor
    Homework Helper

    Proving psi can't have a nontrivial kernel is the whole point. The rest of that is gibberish. The proof has to involve gcd(n,m)=1.
     
  6. Apr 20, 2012 #5
    Does this work???

    Since H is abelian then for all a,b in H we have that (ab)^m = a^m b^m. Thus phi(ab)=(ab)^m = a^m b^m = phi(a)phi(b) so phi is a group homomorphism.

    Since H is finite it suffices to show phi is surjective. Let x be in H , we need to find a in H such that a^m = x.

    By assumption (m,n)=1 so we can find integers u,v such that um + vn = 1.

    But then x = x^1 = x^(um+vn) = x^(um) x^(vn). Since |H|=n then x^n = e (the identity) so x = x^(um).

    Thus taking a = x^u yields phi(a) = a^m = (x^u)^m = x^(um) = x so phi is surjective. Since phi is a surjective endomorphism of a finite group then phi is injective as well, thus an isomorphism.
     
  7. Apr 20, 2012 #6
    Yes, that proof is correct. Well done. Note that you can actually go further here: you have proved that (x^u)^m = x for all x, so that tells you that the inverse homomorphism is the function [itex]x \mapsto x^u[/itex]. In general, if you are given a group homomorphism [itex]\varphi : G \rightarrow H[/itex] and you can find a function [itex]\psi: H \rightarrow G[/itex] such that [itex]\varphi \circ \psi = \mathrm{id}_{H}[/itex] and [itex]\psi \circ \varphi = \mathrm{id}_{G}[/itex], then you have proved that [itex]\varphi[/itex] is an isomorphism and [itex]\varphi^{-1} = \psi[/itex]. This gives you another technique that you can use to prove that a function is an isomorphism.
     
Know someone interested in this topic? Share this thread via Reddit, Google+, Twitter, or Facebook




Similar Discussions: Abstract Algebra: isomorphism proof
Loading...